In silico fragment based design identifies subfamily B1 metallo-β-lactamase inhibitors - Cain, R; Brem, J; Zollman, D; McDonough, M; Johnson, R; Spencer, J; Makena, A; Abboud, M; Cahill, S; Lee, S; McHugh, P; Schofield, C; et al. (American Chemical Society, 2017)
Zinc ion dependent β-lactamases (MBLs) catalyze the hydrolysis of almost all β-lactam antibiotics and resist the action of clinically available β-lactamase inhibitors. We report how application of in silico fragment-based molecular design employing thiol-mediated metal anchorage leads to potent MBL inhibitors. The new inhibitors manifest potent inhibition of clinically important B1 subfamily MBLs, including the widespread NDM-1, IMP-1 and VIM-2 enzymes; with lower potency, some of them also inhibit clinically relevant Class A and D serine-β-lactamases. The inhibitors show selectivity for bacterial MBL enzymes compared to human MBL fold nucleases. Co-crystallization of one inhibitor, which shows potentiation of meropenem activity against MBL-expressing Enterobacteriaceae, with VIM-2 reveals an unexpected binding mode, involving interactions with residues from conserved active site bordering loops.